Samarinda City Government's Commitment to Building and Empowering the Community Through Probebaya - Habibi , Muhammad; Eryani, Trisna Waty Riza; Yani, Ahmad (Manunggal Halim Jaya, 2025)
Community development and empowerment have long been part of the vision and mission of the Indonesian government, from the central level to regional and village governments. This mandate is rooted in the 1945 Constitution of the Republic of Indonesia and further supported by several regulations, including Law No. 25 of 2004 on the National Development Planning System and Law No. 23 of 2014 on Regional Government, as amended by Law No. 9 of 2015. One of the key stages in regional development planning is the musrenbang (development planning deliberation), a participatory planning process. However, not all initiatives can be realized due to the high volume of proposals from the residents. In response to this challenge, Samarinda Mayor Andi Harun and Deputy Mayor Rusmadi, for the 2021–2024 period, introduced the Community Development and Empowerment Program, known as Probebaya. This program aims to strengthen village-level governance, enhance the quality of human resources among officials and residents, empower the local economy, increase environmental awareness, and improve basic infrastructure at the neighborhood (RT) level. Probebaya is a key element in implementing the city's micro-level development mission. This study adopts a qualitative research approach with an exploratory design, delving deeply into Probebaya as a flagship initiative and a tangible expression of the Samarinda City Government's political commitment to its citizens. Data were analyzed using the interactive model by Miles, Huberman, and Saldana (2014). The findings reveal that the Samarinda City Government has fulfilled its political promise of providing a 100 million rupiah development fund for each RT head through Probebaya. The program serves as a commitment to community development and empowerment via a region-based model coordinated at the RT level and implemented through a Type IV self-managed funding scheme. Now in its fifth year, Probebaya has undergone several improvements and refinements. However, challenges remain, particularly in synchronization and harmonization with village partner institutions, whose roles have seemingly been replaced by the growing strength of RT-level community empowerment initiatives. The political promises made during the campaign, along with the challenges posed by the transition from the COVID-19 pandemic to an endemic phase, have required the current Mayor and Deputy Mayor to